Design of Planar Directional Coupler using 2-Bit Fragment Structures - Tao, Yonghui; Zhang, Wenjuan; Sidén, Johan; Wang, Gang (Applied Computational Electromagnetics Society Journal (ACES), 2022)
Automatic design of planar directional coupler can be implemented by multi-objective optimization searching for the optimal planar fragment-type structure (FTS). The 2-bit FTS description scheme may include necessary fine structures in fragments to enhance the FTS design. By coding the coupler design space on PCB in 2-bit FTS, defining the FTS design matrix, and searching for the optimal structure, directional coupler can be designed without any structure presetting or artificial intervention. The scheme is demonstrated by designing 10-dB wideband directional coupler with 2-bit FTS scheme. The designed directional couplers are fabricated and tested to show maximum directivity of 58 dB with 36% operation bandwidth.